Voltage dependence of the cannabinoid CB1 receptor - Esty Goldberger; Merav Tauber; Yair Ben-Chaim (Frontiers Media S.A., 2022)
Cannabinoids produce their characteristic effects mainly by binding to two types of G-protein coupled receptors (GPCRs), the CB1 and CB2 cannabinoid receptors. The CB1 receptor is the main cannabinoid receptor in the central nervous system, and it participates in many brain functions. Recent studies showed that membrane potential may serve as a novel modulatory modality of many GPCRs. Here, we used Xenopus oocytes as an expression system to examine whether membrane potential modulates the activity of the CB1 receptor. We found that the potencies of the endocannabinoid 2-AG and the phytocannabinoid THC in activating the receptor are voltage dependent; depolarization enhanced the potency of these agonists and decreased their dissociation from the receptor. This voltage dependence appears to be agonist dependent as the potency of the endocannabinoid anandamide (AEA) was voltage independent. The finding of this agonist-specific modulatory factor for the CB1 receptor may contribute to our future understanding of various physiological functions mediated by the endocannabinoid system.